Pertumbuhan pacuan pelaburan langsung asing: Ujian sebab-menyebab di Malaysia - Sahlan, Rizaudin; Shakrani, Mohd Saharudin; Zainol, Zairy (Universiti Kebangsaan Malaysia, 2003)
The importance of inflow of foreign direct investment (FDI) to a particular country can be shown in terms of its role in spurring economic growth. Empirical evidence on the FDI and relationship between FDI and economic growth are mixed. While some studies indicate that FDI act as a catalyst to economic growth, some found a reverse relationship between the two.Using a time series data on Malaysia, for the period of 1980-2001, our study tries to identify the direction of the causality between the inflow of FDI and economic growth. We divide the inflow of FDI to Malaysia into four sources: the European Union, NAFTA, Asia-Pacific countries (excluding ASEAN countries), and ASEAN countries. Our study shows that the PLA and economic growth are cointegrated 01- have long-run relationship between them in most cases. Meanwhile, Granger-causality version VECM test analysis shows that FDI from both ASEAN and NAFTA regions are linked bi-directional with economics growth. Meanwhile,Granger-causality is unidirectional, running from economic growth to FDI for the case FDI from European Union. However there is no relationship either unidirectional nor bi-directional between the inflow of FDI from Asia-Pacific regions and the growth of Malaysian economy.